SISTEM INFORMASI DATA KEPENDUDUKAN DINAS PENGENDALIAN PENDUDUK, KELUARGA BERENCANA, PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK (DP2KBP3A) LOMBOK BARAT - Ghazwan Septrian Ahmad; Nadiyasari Agitha; Budi Irmawati (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2022)
Manual data processing leads to difficulty on managing existing data; hard to find and data need to be modified by fill in the form manually. That problem is concerned to lead to an error on data collection and interfere with government of village policy making. Web-based population data information system contains dashboard and data entry will be designed for those problem. This information system built using PHP programming language with CodeIgniter framework and MySQL as database. This information system also adapting Prototype method. This information system designed to help government of village to input and observe population data in order to determine policy and prioritize the problem that occur in the village.